Paulo Coelho’s Hippie: A Critique with Special Reference to Spiritual Aspects - Dr. Arjunsinh K. Parmar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The brief period in which Paulo Coelho lived the hippie lifestyle serves as the backdrop for his novel "Hippy." In the 1960s, those looking for spiritual enlightenment travelled to India and even Nepal hoping to find it there. A subculture in the 1960s was associated with groups with distinctive looks and opposed established conventions. This article's goal is to achieve that goal, and one method it plans to do is by describing how the protagonist grows during his trip and experiences a spiritual awakening after it. The themes of the novel Quest for Spiritual Knowledge are examined in this essay through the prism of popular culture since Paulo Coelho's Hippie is linked to its cultural archetype in contemporary society. This is carried out because the novel is pertinent to the contemporary world. Paulo Coelho's original work's themes of the hero's journey and spiritual education are examined, and those ideas relate to modern popular culture. In Paulo Coelho's book Hippie, Paulo and the other young boys and girls study Western and non-western ideas of culture while making their first forays into the world independently. The hippie movement seems to have been started and coordinated by these young people, who also appear to live in numerous communes and travel widely in search of love, freedom, and peace. They appear to have started the trend as well. I will refer to the works and theories of Joseph Campbell, John Storey, Ray Brown, and Marshall Fishwick to give a theoretical context for my interpretation of the text. Even if the hippie movement develops as a counterculture of the 1960s youth movement, the article contends that the protagonist's quest for spiritual enlightenment merits consideration.